Clinical and Physiological Effects of Rollators in Individuals With Chronic Obstructive Pulmonary Disease: A SYSTEMATIC REVIEW. Issue 6 (November 2018) - Lee, Annemarie L.; Beauchamp, Marla K.; Goldstein, Roger S.; Brooks, Dina
Abstract : Purpose: To determine the effects of using a rollator in people with chronic obstructive pulmonary disease (COPD). Methods: Studies were systematically identified from literature searches of MEDLINE, CINAHL, PEDro, PubMed, EMBASE, and the Cochrane Library databases and the reference lists of included studies. Two reviewers independently selected randomized controlled or crossover studies examining the effects of rollator usage compared with no aid in individuals with COPD. Methodologic quality was assessed by 2 reviewers independently using the Cochrane Risk of Bias tool. Two reviewers also used a customized form to extract characteristics of and outcomes for subjects related to exercise capacity, symptoms, health-related quality of life (HRQOL), physiological, and gait parameters. Weighted mean differences (WMD) with 95% CI were calculated using a fixed-effects model. Results: A total of 7 studies (126 participants) were included. Use of a rollator during a 6-Minute Walk Test (6MWT) improved distance walked (WMD = 13 m; 95% CI, 5-22) and lowered end-6MWT dyspnea rating (WMD = 0.97; 95% CI, 0.63-1.32). Longer-term use did not appear to impact exercise capacity or HRQOL, although this may be related to the frequency of use. Conclusions: When used in the short-term, rollators resulted in a small increase in 6MWT and a reduction in dyspnea. Details on patient adherence are required to accurately evaluate the longer-term effects of rollator usage. Abstract : Supplemental Digital Content is Available in the Text.This systematic review examined the impact of rollator usage in patients with chronic obstructive pulmonary disease on dyspnea and distance walked. Use during a field walking test improved walking distance and reduced dyspnea compared with no aid, but long-term use had no impact on exercise capacity or quality of life.